Education of nurses for primary health care - (:unkn) unknown (My University, 1994)
The preparation of nurses in Turkey for the tasks of the health-for-all strategy has been under way for a number of years. The difficulties encountered, notably in the areas of planning and the training of teachers, together with the approaches to solving them, are outlined below.
Keywords: Turkey; Developing Countries; Asia; Critique; Curriculum; Delivery Of Health Care; Economic Factors; Education; Education, Nursing; Health; Health Education; Health Services; Mediterranean Countries; Needs; Obstacles; Organization And Administration; Primary Health Care; Public Health; Schools; Schools, Nursing; Training Of Trainers; Training Programs; Western Asia